2021
DOI: 10.1093/mnras/stab085
|View full text |Cite
|
Sign up to set email alerts
|

Giant molecular cloud catalogues for PHANGS-ALMA: methods and initial results

Abstract: We present improved methods for segmenting CO emission from galaxies into individual molecular clouds, providing an update to the cprops algorithms presented by Rosolowsky & Leroy. The new code enables both homogenization of the noise and spatial resolution among data, which allows for rigorous comparative analysis. The code also models the completeness of the data via false source injection and includes an updated segmentation approach to better deal with blended emission. These improved algorithms are im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
143
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 136 publications
18
143
1
Order By: Relevance
“…Even though we have used the largest sample to date for the stated scientific goals, the robustness of the analysis is still limited by sample size. Thus, we encourage this result to be verified elsewhere with larger surveys, such as EDGE-CALIFA (Bolatto et al 2017;Sánchez et al 2021) or Physics at High Angular Resolution in Nearby GalaxieS (PHANGS; e.g., Rosolowsky et al 2021;Anand et al 2021;Lee et al 2021). The analysis of SF scaling relations at ∼100 pc from PHANGS was released by Pessa et al (2021) during the review process of this paper and will be analysed elsewhere.…”
Section: The Sfe Is Not Always Diminished In Barssupporting
confidence: 58%
“…Even though we have used the largest sample to date for the stated scientific goals, the robustness of the analysis is still limited by sample size. Thus, we encourage this result to be verified elsewhere with larger surveys, such as EDGE-CALIFA (Bolatto et al 2017;Sánchez et al 2021) or Physics at High Angular Resolution in Nearby GalaxieS (PHANGS; e.g., Rosolowsky et al 2021;Anand et al 2021;Lee et al 2021). The analysis of SF scaling relations at ∼100 pc from PHANGS was released by Pessa et al (2021) during the review process of this paper and will be analysed elsewhere.…”
Section: The Sfe Is Not Always Diminished In Barssupporting
confidence: 58%
“…Table 3 lists the target resolutions and other details of the product creation process. These fixed-resolution cubes are intended to allow rigorous comparison among targets at different distances (e.g., Hughes et al 2013;Rosolowsky et al 2021). The processing described in Section 3 already places the cubes at nearly matched velocity resolution.…”
Section: Data Product Creationmentioning
confidence: 99%
“…Second, convolving to multiple fixed physical resolutions plays a crucial role in testing scientific hypotheses. At the most basic level, this allows for rigorous comparison among galaxies observed with different beams and lying at different distances (e.g., Hughes et al 2013;Rosolowsky et al 2021). Increasingly, spatial scale is also by itself viewed as an important Notes.…”
Section: Convolution To Fixed Resolutionsmentioning
confidence: 99%
“…Considering their beam sizes and the surface densities measured, and assuming that most of the molecular gas emission comes from spiral arms, we would get linear masses in the range of 10 5 10 7 M kpc 1 , more in line with our Milky Way values. Additionally, Rosolowsky et al (2021) performed molecular cloud segmentation for a sample of ten nearby galaxies, observing a spiral arm-inter-arm region molecular gas mass contrast of between ⇠ 1 2.3 (E. Rosolowsky, private communication) considering the mass within clouds, which is similar to what we measure here (1.5, see Section 5.3).…”
Section: Discussion: the Milky Way A Grand-design Or Flocculent Spiral Galaxy?mentioning
confidence: 64%
“…In the barred spiral galaxy M100, the situation is similar: central clouds are more massive, denser, and have higher velocity dispersions than objects in the inter-arm regions (Pan & Kuno 2017). Nevertheless, GMC properties in several other spiral galaxies do not di↵er signficantly from spiral arms to interarm regions (Donovan Meyer et al 2013), even if, more recently, Rosolowsky et al (2021) observed some slightly higher surface densities and lower virial parameters in clouds in the spiral arms compared to objects in inter-arm regions.…”
Section: Introductionmentioning
confidence: 99%